Credibilità e credentità nel Dio di Gesù Cristo - Relja, Hrvoje (Alpha omega, 2011)
It can be philosophically proven that humans have a natural aspiration to see God in His essence. By analyzing that aspiration one can conclude that ‘God can create an intelligent being without directing or calling him toward the beatific vision’, but He cannot create such a being without the possibility to be directed toward the beatific vision. Furthermore, every realistic direction and calling to the beatific vision, i.e. the actualization of that possibility, surpasses every natural possibility of any intelligent being, whether in implementation or in cognition. Therefore, this cognition can be attained only thanks to Revelation. Furthermore, Revelation is historical. It is accomplished through events that contain proof, i.e. convincing arguments in favor of the truth of Revelation. A proof contains signs that are naturally comprehensible to man, but realizable only by a supernatural Revelator, although humans in momentary historical circumstances, characterized by original sin, cannot accept revelation through power of their nature. Therefore, a man, in the momentary situation, in order to realize that which he can according to his nature needs supernatural mercy.